2016
DOI: 10.3233/ch-162043
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological alterations in carotid artery stenosis

Abstract: Although hemorheological parameters are impaired both in CAS and chronic cerebrovascular disorders, the severity of stenosis cannot be detected based on hemorheological parameters. Our investigation suggests that alteration of hemorheological parameters could indicate carotid atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Nevertheless, RBC aggregation has been shown to affect blood flow in both micro- and macro-vessels where shear rate is high, notably because of its effects on several rheological phenomena such as axial migration, cell free layer formation, and the Fahraeus effect, the latter occurring mainly in the microcirculation (Baskurt and Meiselman, 2008 ). Recently, it was shown that patients with symptomatic ischemic cerebral events had increased blood viscosity in comparison to asymptomatic patients (Li et al, 2015 ; Totsimon et al, 2016 ) and healthy controls (Velcheva et al, 2006 ). Lower RBC deformability could be at the origin of this blood hyper-viscosity (Totsimon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, RBC aggregation has been shown to affect blood flow in both micro- and macro-vessels where shear rate is high, notably because of its effects on several rheological phenomena such as axial migration, cell free layer formation, and the Fahraeus effect, the latter occurring mainly in the microcirculation (Baskurt and Meiselman, 2008 ). Recently, it was shown that patients with symptomatic ischemic cerebral events had increased blood viscosity in comparison to asymptomatic patients (Li et al, 2015 ; Totsimon et al, 2016 ) and healthy controls (Velcheva et al, 2006 ). Lower RBC deformability could be at the origin of this blood hyper-viscosity (Totsimon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that patients with symptomatic ischemic cerebral events had increased blood viscosity in comparison to asymptomatic patients (Li et al, 2015 ; Totsimon et al, 2016 ) and healthy controls (Velcheva et al, 2006 ). Lower RBC deformability could be at the origin of this blood hyper-viscosity (Totsimon et al, 2016 ). Research also suggests that RBC aggregation could play a role in ischemic cerebral disease (Zeltser et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown elevated WBV in stroke [6][7][8][28][29][30][31][32][33][34]. However, whether the elevated WBV reduces cerebral reperfusion in stroke has not been definitely established.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] In fact, higher levels of WBV have been reported in stroke groups when compared with healthy control groups. 40,41,[59][60][61][62][63][64][65] More importantly, higher incidence of stroke has been associated with elevated WBV. 40,66,67 In the Edinburgh Artery Study, a prospective study of a randomly selected general population, 1 SD unit increase in WBV increased the risk of stroke by 1.41 times.…”
Section: Microcirculation Disturbances In Strokementioning
confidence: 99%